Effects of an epilepsy‐specific Internet intervention (Emyna) on depression: Results of the ENCODE randomized controlled trial. (25th February 2019) - Meyer, Björn; Weiss, Mario; Holtkamp, Martin; Arnold, Stephan; Brückner, Katja; Schröder, Johanna; Scheibe, Franziska; Nestoriuc, Yvonne
Summary: Objective: Depression and anxiety are highly prevalent among people with epilepsy (PwE) but often remain unrecognized and treated inadequately. Effective psychosocial treatments such as cognitive behavioral therapy (CBT) are rarely available to most PwE, which is one reason electronically delivered CBT (eCBT) is regarded as promising. This study examined an eCBT intervention, termed Emyna, that was tailored to suit the needs of PwE. It includes CBT‐related content on depression, stress and anxiety, seizure triggers and auras, and lifestyle habits. The trial examined the efficacy of Emyna in reducing symptoms of depression (primary outcome) and anxiety as well as improving quality of life. Methods: Participants (N = 200) with epilepsy, a diagnosis of a depressive disorder, and at least moderate depressive symptoms were randomized to Emyna or care as usual. At baseline and after 3, 6, and 9 months, participants were invited to complete online questionnaires. The primary outcome was improvement of depressive symptoms at 3 months. Results: Relative to the control group, intervention group participants experienced significantly greater improvements in depression, anxiety, stress, social‐occupational impairment, and epilepsy‐related quality of life, in both intention‐to‐treat (ITT) and per‐protocol analyses. In ITT analyses, effects of medium magnitude were observed, as measured by the Patient Health Questionnaire–9 items (Cohen d  =   0.54, 95% confidence interval [CI] = 0.25‐0.82, P  <   0.001) and the Neurological Disorders Depression Inventory for Epilepsy ( d  =   0.51, 95% CI = 0.23‐0.79, P  <   0.01). At 3 months, intervention group participants also reported fewer illness‐related days off work and fewer days hospitalized over the preceding months, compared to control group participants ( P  ≤ 0.05), whereas no such differences were present at baseline ( P  > 0.30). Significance: These findings showed that Emyna, used adjunctively to usual care, could help improve mental health, social‐occupational functioning, and quality of life among PwE. The program provides an additional treatment option that could produce clinically relevant symptom reductions and reduce key cost drivers (ie, hospitalization rates and illness‐related inability to work).